2016
DOI: 10.1038/srep37601
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Anticancer Styrylpyrone Biosynthesis in the Medicinal Mushroom Inonotus obliquus Requires Thioredoxin Mediated Transnitrosylation of S-nitrosoglutathione Reductase

Abstract: The medicinal macrofungus Inonotus obliquus widely utilized as folk medicine in Russia and Baltic countries is a source of phenylpropanoid-derived styrylpyrone polyphenols that can inhibit tumor proliferation. Insights into the regulatory machinery that controls I. obliquus styrylpyrone polyphenol biosynthesis will enable strategies to increase the production of these molecules. Here we show that Thioredoxin (Trx) mediated transnitrosylation of S-nitrosoglutathione reductase (GSNOR) underpins the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Similar oxidative pathways for NO generation have also been detected in A. nidulans , A. oryzae (Gorren & Mayer, ), Botrytis cinerea (Turrion‐Gomez & Benito, ) and N. crassa (Ninnemann & Maier, ). Zhao, He, Ding, et al () reported the cloning and heterologous expression of constitutive NOSL and inducible NOSL in the basidiomycetous fungus Inonotus obliquus . Coculture of I. obliquus and Phellinus morii results in enhanced expression of the gene coding for inducible NOSL followed by a burst of NO production.…”
Section: Anabolism Of No In Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Similar oxidative pathways for NO generation have also been detected in A. nidulans , A. oryzae (Gorren & Mayer, ), Botrytis cinerea (Turrion‐Gomez & Benito, ) and N. crassa (Ninnemann & Maier, ). Zhao, He, Ding, et al () reported the cloning and heterologous expression of constitutive NOSL and inducible NOSL in the basidiomycetous fungus Inonotus obliquus . Coculture of I. obliquus and Phellinus morii results in enhanced expression of the gene coding for inducible NOSL followed by a burst of NO production.…”
Section: Anabolism Of No In Fungimentioning
confidence: 99%
“…In I. obliquu s, NO burst not only triggered enhanced expression of PAL, 4‐coumarate CoA ligase (4CL) and styrylpyrone synthase (SPS), which are the key enzymes involved in styrylpyrone biosynthesis and lead to increased styrylpyrone polyphenols production, but also facilitated the formation of NO‐driven protein S ‐nitrosylation. S ‐nitrosylation of PAL and 4CL compromised their enzymatic activities and mediated a posttranslational feedback mechanism that hinders NO‐dependent transcriptional activation (Zhao, He, Ding, et al, ; Zhao, He, Xi, et al, ) (Figure ). However, detailed mechanisms of NO burst‐induced negative regulation of secondary metabolism in molds remain to be elucidated.…”
Section: No and Fungal Secondary Metabolismmentioning
confidence: 99%
“…Understanding of GSNOR, thioredoxin (TRX), and their roles during biosynthesis of phenylpropanoid-derived styrylpyrone polyphenols, components inhibiting tumor proliferation and reducing hypertension and various neurodegenerative disorders [ 96 ], in co-cultured Inonotus obliquus and Phellinus morii might be, in future, employed for medicinal applications. Zhao et al [ 97 ] described the interplay between GSNOR and TRX and their regulation via S-nitrosation/denitrosation and an impact to styrylpyrone biosynthesis. S-nitrosation of the key enzymes in the phenylpropanoid biosynthesis decreases their activity, which can be restored by TRX-mediated denitrosation.…”
Section: The Gsnor Role In Plantsmentioning
confidence: 99%
“…Interestingly, the interplay between GSNOR and TRXs and their regulation via S-nitrosation/ denitrosation have been described within the biosynthesis of phenylpropanoid-derived styrylpyrone polyphenols in the medicinal mushroom Inonotus obliquus [88]. S-nitrosation of the key enzymes in the phenylpropanoid biosynthesis decreases their activity, which can be restored by TRX-mediated denitrosation.…”
Section: Trx Role In Denitrosation Of Plant Proteinsmentioning
confidence: 99%